La mujer como sujeto corporal y reflexivo en el teatro mexicano actual: Dos experiencias, dos miradas, un nuevo síntoma - Azor, Ileana (Latin American Theatre Review, 2003)
This article studies Plagio de palabras by Elena Guiochins and Mme. Cuquita’s Show by Pilar Gallegos in a first approach to two creative women and their styles of discourse which do not belong to the hegemonic Mexican theatre scene. Violence, solitude, the fragmented "I," incommunication, dismanteling sexual stereotypes, uncertainty and the contingent game of past, present and future are themes presented in these two performances that depend on fracturing ideas and scenic space, combining minimalism with puppets and the presence of a confessional discourse that oscillates between irony and black humor. (IA, in Spanish)